Relation of Retinal and Serum Lutein and Zeaxanthin to White Matter Integrity in Older Adults: A Diffusion Tensor Imaging Study. (17th November 2017) - Mewborn, Catherine M; Terry, Douglas P; Renzi-Hammond, Lisa M; Hammond, Billy R; Miller, L Stephen
Abstract: Objective: Lutein (L) and zeaxanthin (Z) are phytonutrients that accumulate in human brain tissue and positively impact cognition. Given their antioxidant and anti-inflammatory properties and their role in stabilizing cell membranes, L&Z may relate to measures of white matter integrity (WMI). Method: The current study tested the relation of retinal (macular pigment optical density/MPOD) and blood serum concentrations of L&Z to WMI in community-dwelling older adults ( n = 54) using diffusion tensor imaging (DTI). Younger adults ( n = 38) were recruited as a control group to confirm age-related changes in WMI. A priori analyses focused on four regions of interest (ROIs—genu of the corpus callosum, cingulum, fornix, and uncinate fasciculus). Exploratory whole-brain analyses were also conducted. Results: Consistent with previous literature, age group (young vs. old) negatively predicted WMI globally, in the genu, cingulum, and fornix ( p < .001). ROI analysis in the older adult sample showed relations of MPOD and serum L&Z to better WMI in the uncinate fasciculus and cingulum ( p < .05, FWE-corrected). Whole-brain analysis suggested associations between L&Z and WMI in both anterior white matter tracts vulnerable to age-related decline and posterior tracts ( p < .01, uncorrected). Conclusions: The current study is among the first to use neuroimaging to measure the relation of L&Z to brain structure in vivo. Results confirm previous findings that L&Z influence white matter integrity, particularly in regions vulnerable to age-related decline. The current study contributes to a growing literature investigating the relationship between diet and neural integrity by identifying white matter tracts that may be associated with modifiable dietary factors in older adults.